Cell type- and time-dependent biological responses in ex vivo perfused lung grafts - Gouin, Carla; Vu Manh, Thien-Phong; Jouneau, Luc; Bevilacqua, Claudia; De Wolf, Julien; Glorion, Matthieu; Hannouche, Laurent; Urien, Céline; Estephan, Jérôme; Roux, Antoine; Magnan, Antoine; Le Guen, Morgan; et al. (Frontiers in Immunology, 2023)
In response to the increasing demand for lung transplantation, ex vivo lung perfusion (EVLP) has extended the number of suitable donor lungs by rehabilitating marginal organs. However despite an expanding use in clinical practice, the responses of the different lung cell types to EVLP are not known.In order to advance our mechanistic understanding and establish a refine tool for improvement of EVLP, we conducted a pioneer study involving single cell RNA-seq on human lungs declined for transplantation. Functional enrichment analyses were performed upon integration of data sets generated at 4 h (clinical duration) and 10 h (prolonged duration) from two human lungs processed to EVLP. Pathways related to inflammation were predicted activated in epithelial and blood endothelial cells, in monocyte-derived macrophages and temporally at 4 h in alveolar macrophages. Pathways related to cytoskeleton signaling/organization were predicted reduced in most cell types mainly at 10 h. We identified a division of labor between cell types for the selected expression of cytokine and chemokine genes that varied according to time. Immune cells including CD4 + and CD8 + T cells, NK cells, mast cells and conventional dendritic cells displayed gene expression patterns indicating blunted activation, already at 4 h in several instances and further more at 10 h. Therefore despite inducing inflammatory responses, EVLP appears to dampen the activation of major lung immune cell types, what may be beneficial to the outcome of transplantation. Our results also support that therapeutics approaches aiming at reducing inflammation upon EVLP should target both the alveolar and vascular compartments.